Directional Delta and Notch trafficking in Sara endosomes during asymmetric cell division. - Coumailleau, F.; Fürthauer, M.; Knoblich, J.A.; González-Gaitán, M. (Nature, 2009)
Endocytosis has a crucial role during Notch signalling after the asymmetric division of fly sensory organ precursors (SOPs): directional signalling is mediated by differential endocytosis of the ligand Delta and the Notch effector Sanpodo in one of the SOP daughters, pIIb. Here we show a new mechanism of directional signalling on the basis of the trafficking of Delta and Notch molecules already internalized in the SOP and subsequently targeted to the other daughter cell, pIIa. Internalized Delta and Notch traffic to an endosome marked by the protein Sara. During SOP mitosis, Sara endosomes containing Notch and Delta move to the central spindle and then to pIIa. Subsequently, in pIIa (but not in pIIb) Notch appears cleaved in Sara endosomes in a gamma-secretase- and Delta internalization-dependent manner, indicating that the release of the intracellular Notch tail to activate Notch target genes has occurred. We thus uncover a new mechanism to bias signalling even before asymmetric endocytosis of Sanpodo and Delta takes place in the daughter cells: already during SOP mitosis, asymmetric targeting of Delta and Notch-containing Sara endosomes will increase Notch signalling in pIIa and decrease it in pIIb.